BASELINE SUSCEPTIBILITY OF LEUCINODES ORBONALIS TO CRY1AC TOXIN USING A DIET-BASED BIOASSAY - PANKAJ B. SALUNKE; SHYAM S. MUNJE; UMESH P. BARKHADE; MANGESH P. MOHARIL (The Bioscan, 2014)
Baseline susceptibility of Brinjal shoot and fruit borer Leucinodes orbonalis to Cry1Ac was elucidate by using diet incorporated bioassay. The results show that, LC50 values during kharif ranged from 0.0326 to 0.0369 mg/mL of diet. The LC50 values from Akola, Amaravati, Washim and Buldhana populations were 0.0369, 0.0363, 0.0349 and 0.0326 mg/ml of diet respectively. The highest LC50 values were observed in Akola population followed by Amaravati and Washim, the lowest LC50 value was observed in Buldhana population. LC90 values of the populations ranges within the baseline limits at 0.0440 to 0.0480 mg/mL of diet. Similarly, LC50 values during Rabi ranged from 0.0322 to 0.0369 mg/mL of diet. The LC50 values from Akola, Amaravati, Washim and Buldhana populations were 0.0349, 0.0369, 0.0339 and 0.0322 mg/mL of diet respectively. The highest LC50 values were observed in Amaravati population followed by Akola and Washim, the lowest LC50 value was observed in Buldhana population and LC90 values of the populations ranges within the baseline limits at 0.0458 to 0.0483 mg/mL of diet.